Remarks on Receiving the 2000 Distinguished Service Award - R. Gary Rotier, DDS, MPH (Blackwell Synergy, 2001)
Thank you very much for those comments, Alex. I was pleased to learn that Alex would be presenting this award because he has a very warm and personal way of doing these presentations. Alex and I grew up about 20 miles (and probably about 20 years) from each other in a very rural part of North Carolina. Here, my family was always prepared for someone to stop by unexpectedly for Sunday dinner, everyone always came to the back door, which was never locked, and everythmg in town-church, school, shopping, and health care-was within a short 15-minute walk.